"Fury, us": Anger as a basis for new group self-categories. Issue 1 (2nd January 2016) - Livingstone, Andrew G.; Shepherd, Lee; Spears, Russell; Manstead, Antony S. R.
Abstract : We tested the hypothesis that shared emotions, notably anger, influence the formation of new self-categories. We first measured participants' ( N = 89) emotional reactions to a proposal to make university assessment tougher before providing feedback about the reactions of eight other co-present individuals. This feedback always contained information about the other individuals' attitudes to the proposals (four opposed and four not opposed) and in the experimental condition emotion information (of those opposed, two were angry, two were sad). Participants self-categorised more with, and preferred to work with, angry rather than sad targets, but only when participants' own anger was high. These findings support the idea that emotions are a potent determinant of self-categorisation, even in the absence of existing, available self-categories.